PENDEKATAN MAQASHID SHARIAH INDEX SEBAGAI PENGUKURAN KINERJA PERBANKAN SYARIAH DI ASIA TENGGARA - Mutia, Evi; Musfirah, Nastha (Jurnal Akuntansi dan Keuangan Indonesia, 2017)
This study aims to analyze the performance of Islamic banking in Southeast Asian countries using maqashid shariah index. The performance assessment of Islamic banking is usually only seen from the measurement of financial performance. In this study, the performance of Islamic banking will be measured in terms of the purpose of using the concept maqashid shariah index advanced by Abdul Majid Najjar which presents a concept maqashid shariah more widely and effectively by divide it into four objectives and eight elements. This type of research is quantitative descriptive. The object of the research is an Islamic commercial bank in the Southeast Asian countries (Indonesia, Malaysia, Brunei, Thailand and the Philippines) which have 25 Islamic banks. Data used is secondary data in the form of financial statements or annual reports that obtained from the official website of each bank. By using maqashid shariah index and the methods of SAW (Simple Additive Weighting), it can be concluded that Indonesia has the best performance in the amount of 46.22%, followed by Malaysia amounted to 43.15%, Brunei Darussalam by 37.54%, Thailand amounted to 17.51%, and Philippine amounted to 1.12%.